Perancangan Sistem Pengendalian Risiko Menggunakan Simplified Bowtie Analysis pada Fasilitas FSO Federal II di PT XYZ - Purwanto, Shaula Irlandy Ramadhania; Yunita Nugrahaini Safrudin; Hadi Susanto (Dinasti Research, 2024)
The oil and gas industry in Indonesia, including PT XYZ which manages domestic oil and gas, faces high complexity and risk. PT XYZ's operations are supported by several offshore platforms and facilities which have various potential risks. Process safety is a top priority to prevent major incidents or major accidents. PT XYZ uses Process Hazard Analysis (PHA) which needs to be revalidated every five years to ensure procedures comply with current conditions. This research focuses on the FSO Federal II facility owned by PT XYZ, a 200 thousand barrel capacity crude oil storage vessel with a high potential risk of major incidents. PT XYZ uses the HAZOP and HAZID methods in PHA to identify risks. However, PT XYZ does not yet have a direct control system for workers. This research aims to create a risk control system that can be used by Federal II FSO workers as a work guide. This work guide will help in handling undesirable events that have the potential to cause major incidents. Proposed improvements include creating a work guidance document based on risk identification using Bowtie Analysis, which produces a mapping diagram of causes, peak events, hazards and consequences. The bowtie diagram will be simplified to make things easier for workers, considering the large number of processes in FSO Federal II. This guideline will help workers prevent major incidents from occurring.